La critique de l’univers de Peurbach développée par Albert de Brudzewo a-t-elle influencé Copernic ? Un nouveau regard sur les réflexions astronomiques au XVe siècle - Malpangotto, Michela (Almagest, 2013)
Abstract In 1454 Georg Peurbach teaches astronomy at the Collegium Civium in Wien by reading a work of his own: the Theoricae novae planetarum. Intended to replace the old Theorica planetarum communis which had dominated the mediaeval culture, this new book is very soon adopted in the major universities of Europe and enjoys a broad diffusion being published, studied and taught up to the middle of the 17th century. Among the numerous commentaries which have been preserved -both in manuscript and printed form- the tradition of the Cracow University, started by Albert of Brudzewo, distinguishes itself because it submit Peurbach’s contribution to a subtle critique which, while recognizing the merits to which its large acceptance is due, focuses also its limits. In the name of the reality of the celestial world, Brudzewo critiques the presence, in the universe of the Theoricae, of abstract entities like the equant and the mean apogee, to which the uniformity of the movements must be referred according to an active interaction with the “real” orbs. In the name of the celestial perfection, he grasps the weaknesses and incoherences of Peurbach’s universe and arrives, ultimately, to question this point of view which acts as the mean between the real celestial world and the way it appear to an observer. In this paper, I will try to show that what was strongly supported by Brudzewo as a requirement which must be respected -i.e. the perfect uniformity and circularity of celestial movements- becomes, in Copernicus, the reason to research an alternative solution: “a more reasonable model composed of circles from which every apparent irregularity would follow while everything in itself moved uniformly, just as the principle of perfect motion requires”. So, the better known among the students of the Cracow school proves that it is not only possible, but even necessary to make astronomy from a new point of view.